Determination of Exponential Smoothing Constant to Minimize Mean Square Error and Mean Absolute Deviation (Global Journals of Research in Engineering, 2011)
Exponential smoothing technique is one of the most important quantitative techniques in forecasting The accuracy of forecasting of this technique depends on exponential smoothing constant Choosing an appropriate value of exponential smoothing constant is very crucial to minimize the error in forecasting This paper addresses the selection of optimal value of exponential smoothing constant to minimize the mean square error MSE and mean absolute deviation MAD Trial and error method is used to determine the optimal value of exponential smoothing constant An example is presented to discuss the method